The role and function of microRNAs in the nervous system - Martin, Clare Alice (2019)
In this thesis, novel functions for miRNAs in nervous system processes are characterised. It has been shown that miRNAs have the potential to play an important role in all aspects of the nervous system, from development and function to neurodegeneration. Reflecting on this breadth of possible roles for miRNAs, this is a thesis of two interconnected projects. Firstly, miRNAs with possible novel roles in inflammatory nociceptive processes were identified, and secondly, miRNAs with novel functions in nervous system development and function are investigated through the model system of Drosophila.